Um estudo sobre o câncer de mama e a terapia por captura de nêutrons pelo Boro utilizando modelagem fuzzy - Silva, Ellen Vilarinho da (Universidade Federal de São Carlos, 2022)
This Course Conclusion Paper brings cancer, which is currently one of the biggest public health problems in the world, as the main theme. Breast cancer is the most frequent among women, accounting for 2,1 million cases in 2018. Due to the urgency that the topic brings, the objective of this work was to develop two mathematical models using the Fuzzy Set Theory. The first model contributes to an accurate classification of the Breast Imaging Data Reporting System (BI-RADS), considering tumor doubling time and other characteristics such as shape, contour and density. The second model refers to Boron Neutron Capture Therapy (BNCT), which is a promising treatment for cancer treatment. BNCT uses targeted radiation with irradiated neutron beams, and due to the high selectivity of the 10B, only tumor cells are destroyed. In this modeling, important aspects related to the disease were incorporated, such as depth, distance to the heart and also the volume of the breast, to predict the concentration of 10B in the tumor. Systems based on fuzzy rules (SBRF) allow the consideration of subjective terms intrinsic to examinations and medical procedures, providing comprehensible data for specialists and assisting in the decision-making process. The results achieved in this study show that both models can be useful, contributing to the diagnosis and treatment of malignant breast tumors.
A study on breast cancer and Boron neutron capture therapy using fuzzy modeling
Keywords: Câncer de Mama; Modelagem Matemática; Lógica Fuzzy; Terapia por Captura de Nêutrons pelo Boro; Breast Cancer; Mathematical Modeling; Fuzzy Logic; Boron Neutron Capture Therapy; CIENCIAS EXATAS E DA TERRA::FISICA